Strategi dan Etika Dakwah Rasulullah SAW - Syamsudin RS (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2009)
Trip missionizes crowded rasulullah saw empirically fruitfulness. Strategy missionizes that reflect ethical point and gives motodis's framework universal is of important to be made reference and guidance by pengemban missionizes and be made as model of mission that have normative kontekstual's historical force. Severally behavioural ethical prophet which can make universal a figure of speech in missionizes for example (1 ) really regard situations and condition of, (2 ) Advances ahlakul karimah in acts, (3 ) Paying Attention impacts or effect of spontaneous actions.